(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the influence of whey feeding on cheese powder associated with industrial waste milk on the characteristics, yields and quality of meat of dairy calves. Forty male calves were distributed in four treatments and ten replications: WM - whole milk (control); MPW0 - 100% milk powder; MPW20 - 80% Milk Powder + 20% Cheese Whey and MPW40 - 60% Milk Powder + 40% Cheese Whey. In the carcass, the values ​​of pH and slaughter temperature were evaluated and after 24 hours of cooling. The physicochemical parameters, water activity, acidity, humidity, ashes, proteins and lipids of meat were evaluated in the Longissimus dorsi muscle. The average pH of the carcass after slaughter was 6.6 and the pH after cooling 5.3. The average values ​​of moisture, protein, ether extract and ash were: 73.36%; 23.03%; 2.00% and 1.06%, respectively. In the sensory analysis were evaluated color, softness, taste, juiciness, overall impression and purchase intention, showed no significant difference. The tested diets did not affect carcass characteristics, tissue composition and qualitative attributes of meat of the evaluated animals. It is possible to substitute whole milk for diets based on whey cheese powder and milk and did not impair the development of meat. lactating dairy calves.